HUBUNGAN HARGA DIRI DAN DUKUNGAN SOSIAL KELUARGA DENGAN KEMATANGAN KARIR SISWA KELAS XI DI SMA NEGERI 58 JAKARTA: HUBUNGAN HARGA DIRI DAN DUKUNGAN SOSIAL KELUARGA DENGAN KEMATANGAN KARIR SISWA KELAS XI DI SMA NEGERI 58 JAKARTA - Wulandari, Try; Nurhadianti, Rr. Dini Diah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACTThis research aims to know the relationship between self esteem and family social support with career maturity ofeleventh-grade students in SMAN 58 Jakarta. The sampling technique used was probability simple random sampling witha population of 288 students and research sample of 120 students based on Nomogram Harry King. The data collectiontechnique was used in three scales, i.e., career maturity, self esteem, and family social support. The collected data wereanalized by using Pearson Product Moment Correlation. The result of bivariate correlation data analysis on variables of selfesteem with career maturity was obtained correlation coefficient value (rxy1) = 0,496 with p < 0,05. So, (Ha1) which means“There is a relationship of self esteem with career maturity of eleventh-grade students in SMAN 58 Jakarta” is accepted.The result of bivariate correlation data analysis on variables of family social support with career maturity was attainedcorrelation coefficient value (rxy2) = 0,307 with p < 0,05. So, (Ha2) which means “There is a relationship of family socialsupport with career maturity of eleventh-grade students in SMAN 58 Jakarta” is accepted. The result of multivariatecorrelation data analysis on variables of self esteem and family social support with career maturity was gained R = 0,497with p < 0,05. (Ha3) which means “There is a relationship of self esteem and family social support with career maturity ofeleventh-grade students in SMAN 58 Jakarta” is accepted.